NHP2 deficiency impairs rRNA biogenesis and causes pulmonary fibrosis and Høyeraal–Hreidarsson syndrome. (27th January 2020) - Benyelles, Maname; O'Donohue, Marie-Françoise; Kermasson, Laëtitia; Lainey, Elodie; Borie, Raphael; Lagresle-Peyrou, Chantal; Nunes, Hilario; Cazelles, Clarisse; Fourrage, Cécile; Ollivier, Emmanuelle; Marcais, Ambroise; Gamez, Anne-Sophie; et al.
Abstract: Telomeres are nucleoprotein structures at the end of chromosomes. The telomerase complex, constituted of the catalytic subunit TERT, the RNA matrix h TR and several cofactors, including the H/ACA box ribonucleoproteins Dyskerin, NOP10, GAR1, NAF1 and NHP2, regulates telomere length. In humans, inherited defects in telomere length maintenance are responsible for a wide spectrum of clinical premature aging manifestations including pulmonary fibrosis (PF), dyskeratosis congenita (DC), bone marrow failure and predisposition to cancer. NHP2 mutations have been so far reported only in two patients with DC. Here, we report the first case of Høyeraal–Hreidarsson syndrome, the severe form of DC, caused by biallelic missense mutations in NHP2 . Additionally, we identified three unrelated patients with PF carrying NHP2 heterozygous mutations. Strikingly, one of these patients acquired a somatic mutation in the promoter of TERT that likely conferred a selective advantage in a subset of blood cells. Finally, we demonstrate that a functional deficit of human NHP2 affects ribosomal RNA biogenesis. Together, our results broaden the functional consequences and clinical spectrum of NHP2 deficiency.